A Mobile Game Platform for Improving Social Communication in Children with Autism: A Feasibility Study - Penev, Yordan; Dunlap, Kaitlyn; Husic, Arman; Hou, Cathy; Washington, Peter; Leblanc, Emilie; Kline, Aaron; Kent, John; Ng-Thow-Hing, Anthony; Liu, Bennett; Harjadi, Christopher; Tsou, Meagan; Desai, Manisha; Wall, Dennis P. (Applied Clinical Informatics, 2021)
Background Many children with autism cannot receive timely in-person diagnosis and therapy, especially in situations where access is limited by geography, socioeconomics, or global health concerns such as the current COVD-19 pandemic. Mobile solutions that work outside of traditional clinical environments can safeguard against gaps in access to quality care.Objective The aim of the study is to examine the engagement level and therapeutic feasibility of a mobile game platform for children with autism.Methods We designed a mobile application, GuessWhat, which, in its current form, delivers game-based therapy to children aged 3 to 12 in home settings through a smartphone. The phone, held by a caregiver on their forehead, displays one of a range of appropriate and therapeutically relevant prompts (e.g., a surprised face) that the child must recognize and mimic sufficiently to allow the caregiver to guess what is being imitated and proceed to the next prompt. Each game runs for 90 seconds to create a robust social exchange between the child and the caregiver.Results We examined the therapeutic feasibility of GuessWhat in 72 children (75% male, average age 8 years 2 months) with autism who were asked to play the game for three 90-second sessions per day, 3 days per week, for a total of 4 weeks. The group showed significant improvements in Social Responsiveness Score-2 (SRS-2) total (3.97, p <0.001) and Vineland Adaptive Behavior Scales-II (VABS-II) socialization standard (5.27, p = 0.002) scores.Conclusion The results support that the GuessWhat mobile game is a viable approach for efficacious treatment of autism and further support the possibility that the game can be used in natural settings to increase access to treatment when barriers to care exist.
Keywords: digital therapeutics; mobile game; mobile health; AI-medicine; autism spectrum disorder; developmental disorders; behavioral therapy; clinical testing; smartphone; patient population; mental health